2010
DOI: 10.4269/ajtmh.2010.09-0520
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological, Serological, and Molecular Confirmation of Indigenous Alveolar Echinococcosis Cases in Mongolia

Abstract: Alveolar echinococcosis cases diagnosed histopathologically in 2002, 2006, 2007, and 2009 in Ulaanbaatar, Mongolia were reconfirmed by evaluating the cytochrome c oxidase subunit I gene of mitochondrial DNA. The most recent three cases using paraffin-embedded and ethanol-fixed specimens revealed that one was of the “Asian” haplotype, whereas two others were of the “Inner Mongolian” type. All patients were born in the western provinces of Mongolia, they never resided outside of Mongolia, and they were given a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…In the past three decades, Echinococcus multilocularis , the causative agent of human alveolar echinococcosis (AE), has been newly reported in countries of Europe (Davidson et al 2012) and discovered in foci of relatively high incidence in China and neighbouring countries of Central Asia and Siberia (Craig et al 1992; Ito et al 2003, 2010; Li et al 2005; Yang et al 2006; Torgerson et al 2009; Ziadinov et al 2011; Konyaev et al 2012). Although the distribution range of the parasite is described as being widespread in the northern hemisphere, large regional gaps and differences are observed.…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, Echinococcus multilocularis , the causative agent of human alveolar echinococcosis (AE), has been newly reported in countries of Europe (Davidson et al 2012) and discovered in foci of relatively high incidence in China and neighbouring countries of Central Asia and Siberia (Craig et al 1992; Ito et al 2003, 2010; Li et al 2005; Yang et al 2006; Torgerson et al 2009; Ziadinov et al 2011; Konyaev et al 2012). Although the distribution range of the parasite is described as being widespread in the northern hemisphere, large regional gaps and differences are observed.…”
Section: Introductionmentioning
confidence: 99%
“…So far five cases of AE have been documented in four provinces, mainly in the northwest of Mongolia (Ito and Budke, 2015). Molecular studies from metacestodes of three AE patients revealed both Asian and the Mongolian E. multilocularis haplotypes (Ito et al, 2010). p0540…”
Section: 2 Infections In Animalsmentioning
confidence: 99%
“…Thus, we were able to identify E. vogeli in this sample. This underlines the difficulty of DNA extraction from FFPE (degradation of DNA and low yield of extraction of long DNA fragments) and the need for shorter PCR targets for identification of infectious agents using PCR and sequencing in FFPE tissue (16)(17)(18)). An alternative quantitative PCR (qPCR) approach that targets short mitochondrial DNA fragments could also be of interest on FFPE DNA extract, either by combining species-specific targets or by defining genus-specific system, followed by melting curve analysis for species diagnosis (19,20).…”
mentioning
confidence: 99%